The Relationship Between Digital Parenting and Children's Moral Development in the Technological Era - Adella, Shinta (PT. Anagata Sembagi Education, 2025)
The transformation of parenting patterns in the digital era reflects a fundamental paradigm shift in the relationship between parents and children that no longer only takes place in physical space, but also penetrates the virtual realm that is full of value ambiguity. Digital parenting is not just about mastering technology, but also demands reflective, participatory, and ethical abilities from parents to guide children in navigating the digital world. This study uses a qualitative approach with a literature study method to examine the relationship between digital parenting patterns and children's moral development amidst the onslaught of instant global information and values. The findings show that the digital literacy gap between generations and the lack of value-based parenting approaches are the main factors in weakening children's moral formation. In this context, adaptive parenting strategies require active parental involvement through value mediation, dialogic communication, and strengthening digital moral literacy. The digital space that has become an agent of value socialization implicitly demands the critical presence of adults as ethical facilitators, not just technical controllers. This study emphasizes the urgency of reconstructing the parenting paradigm towards a model that is responsive to the moral challenges of the technological era, as well as the importance of collaboration between families, schools, and communities in forming an ethical and reflective digital parenting ecosystem.